Directional takeoff, aerial righting, and adhesion landing of semiaquatic springtails - Ortega-Jimenez, Victor M.; Challita, Elio J.; Kim, Baekgyeom; Ko, Hungtang; Gwon, Minseok; Koh, Je Sung; Bhamla, M. Saad (Proceedings of the National Academy of Sciences of the United States of America, 2022)
Springtails (Collembola) have been traditionally portrayed as explosive jumpers with incipient directional takeoff and uncontrolled landing. However, for these collembolans that live near the water, such skills are crucial for evading a host of voracious aquatic and terrestrial predators. We discover that semiaquatic springtails, Isotomurus retardatus, can perform directional jumps, rapid aerial righting, and near-perfect landing on the water surface. They achieve these locomotive controls by adjusting their body attitude and impulse during takeoff, deforming their body in midair, and exploiting the hydrophilicity of their ventral tube, known as the collophore. Experiments and mathematical modeling indicate that directional-impulse control during takeoff is driven by the collophore’s adhesion force, the body angle, and the stroke duration produced by their jumping organ, the furcula. In midair, springtails curve their bodies to form a U-shape pose, which leverages aerodynamic forces to right themselves in less than ∼20 ms, the fastest ever measured in animals. A stable equilibrium is facilitated by the water adhered to the collophore. Aerial righting was confirmed by placing springtails in a vertical wind tunnel and through physical models. Due to these aerial responses, springtails land on their ventral side ∼85% of the time while anchoring via the collophore on the water surface to avoid bouncing. We validated the springtail biophysical principles in a bioinspired jumping robot that reduces in-flight rotation and lands upright ∼75% of the time. Thus, contrary to common belief, these wingless hexapods can jump, skydive, and land with outstanding control that can be fundamental for survival.
Keywords: Animals; Arthropods; Biomechanical Phenomena; Rotation; Water; aerial righting; interfacial locomotion; jumping control; landing; springtails